Ameliorative effect of sesamin in cisplatin-induced nephrotoxicity in rats by suppressing inflammation, oxidative/nitrosative stress, and cellular damage - Ali, B H; Al Salam, S; Al Suleimani, Y; Al Za'abi, M; Ashique, M; Manoj, P; Sudhadevi, M; Al Tobi, M; Nemmar, A (Physiological research, 2020)
Nephrotoxicity of cisplatin (CP) involves renal oxidative stress and inflammation, and sesamin (a major liganin in many plants) has strong antioxidant and antiinflammatory actions. Therefore, we investigated here the possible mitigative action of sesamin on CP nephrotoxicity in rats. Sesamin was given orally (5 mg/kg/day, 10 days), and on the 7th day, some of the treated rats were injected intraperitoneally with either saline or CP (5 mg/kg). On the 11th day, rats were sacrificed, and blood and urine samples and kidneys were collected for biochemical estimation of several traditional and novel indices of renal damage in plasma and urine, several oxidative and nitrosative indices in kidneys, and assessment of histopathological renal damage. CP significantly and adversely altered all the physiological, biochemical and histopathological indices of renal function measured. Kidneys of CP-treated rats had a moderate degree of necrosis. This was markedly lessened when CP was given simultaneously with sesamin. Sesamin treatment did not significantly alter the renal CP concentration. The results suggested that sesamin had ameliorated CP nephrotoxicity in rats by reversing the CP-induced oxidative stress and inflammation. Pending further pharmacological and toxicological studies sesamin may be considered a potentially useful nephroprotective agent.
Keywords: dioxoly; Plant Extracts; Drug Evaluation, Preclinical; preklinické hodnocení léčiv; Phytotherapy; cisplatina; fytoterapie; nemoci ledvin; Cisplatin; ledviny; Antineoplastic Agents; Kidney; Sesamum; Antioxidants; zvířata; rostlinné extrakty; potkani Wistar; antioxidancia; Rats, Wistar; Male; lignany; Dioxoles; protinádorové látky; Animals; mužské pohlaví; Lignans; Kidney Diseases